Ice work - Wilson, Robin (2002)
Pista de patinaje sobre hielo en Grenobel, Francia, por los arqs. <Hérault-Arnod Architectes>
Keywords: FRANCIA; GRENOBLE; HÉRAULT, ISABEL; ARNOD, YVES; ARQUITECTURA DEPORTIVA; PISTAS DE PATINAJE